A kind of steam erosion resistant protective coating and preparation method thereof
By adopting the gradient alloy material design with the principle of "internal toughness and external hardness" in the hydroelectric unit coating, the problem of difficulty in protecting cavitation and abrasion at the same time in the prior art is solved, and the excellent anti-vapor abrasion performance and protective effect of the coating are achieved.
Patent Information
- Application Number
- CN202211385219.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-11-07
AI Technical Summary
The prior art is difficult to effectively protect the water-electric unit from coupling damage caused by cavitation and abrasion, resulting in poor damage resistance of steam abrasion resistance and easy peeling failure in actual applications of the coating.
Design a protective coating that is resistant to vapor abrasion, adopts the principle of ‘internal toughness and external hardness’. Through the design of gradient alloy materials, the coating surface has high hardness to resist wear, and the internal alloy has high elastic modulus and tough plasticity, which can absorb or buffer cavitation impact energy.
The coating has excellent anti-warming properties in the hydroelectric unit, meets the protection needs, and avoids the problem of the coating being easily peeled and failed.
Smart Images

Figure CN115948734B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface strengthening, and in particular relates to an anti-steam erosion protective coating and a preparation method thereof. Background Art
[0002] The combined damage caused by cavitation and abrasion is one of the more common faults of hydropower units. In actual situations, this combined damage is mainly concentrated in areas such as turbine runner blades, guide vanes, tailwater pipes, bottom rings, and the inner wall of the runner chamber.
[0003] Cavitation and abrasion interact with each other and influence each other, forming a complex joint destructive effect. Specifically, high-frequency cavitation leads to fatigue damage on the surface of the material, forming microscopic pits, cracks and other defects; the impact of flowing sand cutting leads to defect peeling, forming a macroscopic rough concave-convex morphology; and this concave-convex morphology will further increase the gas core density, aggravate the formation of micro-area cavitation vortices and low-pressure conditions, and cause more serious cavitation. Therefore, it should be pointed out that cavitation-abrasion composite damage is different from general abrasion / wear, corrosion, thermal shock / erosion and other damages, and they cannot be generalized. Although some coatings in the prior art can solve problems such as abrasion / wear and corrosion, they cannot solve the cavitation problem at the same time.
[0004] Therefore, it is necessary to conduct in-depth research on coating materials in order to obtain protective coatings that can effectively resist steam erosion. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems: in view of the special working conditions faced by hydropower units, the protective coating that can be used must meet the performance requirements of anti-cavitation and anti-abrasion at the same time. In general, the higher the surface hardness of the coating material, the stronger its ability to resist damage such as sand micro-cutting, friction and wear; the larger the elastic modulus of the coating material, the better the toughness and plasticity, the stronger its ability to buffer and absorb impact energy, the smaller the defects caused by fatigue damage, and the stronger its ability to resist impact effects such as cavitation shock waves and microjets. However, in classical materials, hardness is often contrary to toughness and plasticity. High hardness often leads to a decrease in fatigue toughness and an increase in brittleness of the material, and it cannot effectively resist high-frequency impacts of cavitation; high elastic modulus can buffer and absorb impact energy and bounce off impacting mud and sand to reduce plastic deformation and fatigue damage, but wear resistance is often poor.
[0006] For example, the common protective coatings for hydropower units currently include ceramic materials, alloy materials, organic materials, composite materials, etc., which can be prepared by thermal spraying, laser cladding, surfacing, coating and other methods, but generally have problems such as poor resistance to steam erosion coupling damage and easy peeling failure. Specifically, ceramic materials generally have high hardness characteristics, but poor toughness and plasticity, and poor cavitation resistance; organic materials have good toughness and plasticity, but the bonding strength with components and tear resistance and wear resistance are average. Therefore, in the material design and preparation stage, handling the relationship between hardness, toughness and elasticity is the key to improving the comprehensive steam erosion resistance of the coating.
[0007] In summary, the current research on anti-steam erosion protective coatings is not sufficient, and it is urgent to develop a hydropower unit protective coating suitable for complex working conditions of steam erosion coupling, with excellent hardness and toughness and plasticity, and its preparation method.
[0008] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention proposes a steam erosion resistant protective coating and a preparation method thereof, wherein a gradient alloy material is designed according to the principle of "tough inside and hard outside", wherein the surface layer of the coating with a high strengthening component content has a high hardness to resist mud and sand cutting wear, and the internal alloy of the coating with a low strengthening component content has a high elastic modulus and good toughness and plasticity, which can play the role of tissue phase transformation absorption or elastic buffering to dissipate cavitation impact energy, thereby making the coating have excellent steam erosion resistance and meet the protection needs of hydropower machinery.
[0009] The anti-steam erosion protective coating of the embodiment of the present invention includes at least four layers, each layer is prepared by laser printing of composite powder, and the total mass of the composite powder is 100%, and the composite powder includes component A, component B and optionally component C. In the composite powder of each layer, the mass fraction of component A decreases from the bottom layer to the surface layer, and the mass fraction of component B increases from the bottom layer to the surface layer. The mass fraction difference of component B between adjacent layers is 1 to 25%; component A includes at least one of Fe-based alloys, Ni-based alloys, Co-based alloys, and high-entropy alloys, and component B includes at least one of carbides, oxides, nitrides or borides and optionally a bonding alloy, and component C is a rare earth oxide.
[0010] The advantages and technical effects of the anti-steam erosion protective coating of the embodiment of the present invention are as follows:
[0011] (1) Compared with single metal, ceramic or other coatings, the coating provided by the embodiment of the present invention combines metal and ceramic materials into one, and the coating has the advantages of high hardness and good toughness of both materials, and is more suitable for the protection of cavitation and abrasion coupling damage;
[0012] (2) The present invention designs a gradient alloy material according to the principle of "tough inside and hard outside". The surface layer of the coating with a high strengthening component content has a high hardness to resist mud and sand cutting wear, and the internal alloy of the coating with a low strengthening component content has a high elastic modulus and good toughness and plasticity, which can play the role of structural phase transformation absorption or elastic buffering to dissipate cavitation impact energy, so that the coating has excellent anti-cavitation erosion performance;
[0013] (3) In the coating provided by the embodiment of the present invention, in the composite powder of each layer, the component B has at least 4 different mass fractions, and the mass fraction difference of the component B between adjacent layers is 1 to 25%. The reasonable number of layers and the mass fraction difference of the component B between adjacent layers make the bonding and matching between the layers of the coating excellent, making the microstructure and performance more uniform, and ultimately improving the anti-steam erosion performance of the coating.
[0014] In some embodiments, the coating has 4 to 15 layers; preferably, the coating has 5 to 13 layers.
[0015] In some embodiments, the mass fraction of component B changes in an arithmetic progression from the bottom layer to the surface layer, and the tolerance is 3-20%, preferably 3-10%.
[0016] In some embodiments, in the bottom layer, based on the total mass of the composite powder being 100%, the mass fraction of component A is 96-100%, and the mass fraction of component B is 0-2.5%; in the surface layer, based on the total mass of the composite powder being 100%, the mass fraction of component A is 20-70%, and the mass fraction of component B is 30-80%;
[0017] In some embodiments, preferably, in the bottom layer, based on the total mass of the composite powder being 100%, the mass fraction of component A is 96-100%, and the mass fraction of component B is 0-2.5%; in the surface layer, the mass fraction of component A is 38-54%, and the mass fraction of component B is 46-62%;
[0018] In some embodiments, more preferably, in the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 98-100%, and the mass fraction of component B is 0-0.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 40-51%, and the mass fraction of component B is 48-60%.
[0019] In some embodiments, based on the total mass of the composite powder being 100%, the mass fraction of component C is 0 to 4%, preferably 0 to 2%.
[0020] In some embodiments, the average particle size of component A is in the range of 50 to 200 μm, the average particle size of component B is in the range of less than or equal to 50 μm, and the average particle size of component C is in the range of less than or equal to 20 μm. Preferably, component C is nanoparticle size.
[0021] In some embodiments, the carbide includes at least one of WC, Cr3C2, SiC, and TiC, the nitride includes BN and / or TiN, the boride includes at least one of SiB6, Al2O3, SiO2, and TiO2, the bonding alloy includes at least one of Ni, Co, and Cr bonding alloys, and the rare earth oxide includes at least one of La2O3, CeO2, Y2O3, and Er2O3.
[0022] The present invention also provides a method for preparing a steam erosion resistant protective coating, comprising the following steps:
[0023] (1) Preparation of composite powder: Component A, component B and component C are placed in three powder storage tanks respectively, and the control device sprays the component A, component B and optional component C in a specified mass ratio into the mixing tank in multiple times according to the set program, and the composite powders with a series of content ratios are formed after being stacked multiple times; or the composite powders with a series of content ratios are directly and continuously input into the laser printing device without passing through the powder storage tank;
[0024] (2) Surface treatment of energy components: The damaged parts of energy components are first repaired by welding or laser printing and then processed to be smooth. The surface is then derusted and degreased, and dried for use.
[0025] (3) Laser printing: The laser printing device is configured to be a front and rear dual laser series mode, wherein the front laser performs laser preheating on the surface of the energy component or the upper layer of the coating, and the rear laser adopts a coaxial powder feeding laser printing mode to prepare a coating on the surface area of the energy component that is fully preheated. The composite powders with a series of content ratios are rapidly melted, sintered or solidified and sequentially superimposed to prepare a metallurgical composite material with a gradient distribution characteristic;
[0026] (4) Optionally, coating strengthening treatment: performing stress removal and surface polishing treatment on the coating.
[0027] The advantages and technical effects of the method for preparing the anti-steam erosion protective coating according to the embodiment of the present invention are as follows:
[0028] (1) Compared with the traditional metal / ceramic layer composite method, the coating provided by the present invention is prepared by a laser printing method. The composition gradient of the coating changes continuously, the interlayer defects are few and the bonding is good. The interlayer cracking problem is not easy to occur under high-frequency impact;
[0029] (2) The laser printing process is highly automated, flexible and controllable. The resulting coating has high metallurgical bonding strength, few defects and low dilution rate, making it suitable for coating protection of parts with complex shapes.
[0030] (3) During the laser printing process, preheating and laser printing are completed quickly one after another, ensuring stable coating quality, excellent bonding, and reducing the tendency of thermal stress cracking in the coating.
[0031] In some embodiments, in step (3), the preheating temperature of the front laser is 80-200°C, the rear laser adopts a CO2 laser or a YAG laser, and the process parameters of the rear laser are set as follows: laser power is 0.5-8KW, spot size is Φ0.5-5mm, scanning rate is 0.1-10m / min, overlap rate is 30%-80%, powder feeding speed is 5-100g / min, single pass printing thickness is 0.1-2.0mm, total coating thickness is 0.2-20mm, and inert gas protection is optional.
[0032] In some embodiments, preferably, the laser power of the bottom layer is 0.5-3 KW, and the laser power of subsequent layers increases in an arithmetic progression with a tolerance of 0.1-0.5 KW.
[0033] In some embodiments, in step (4), the coating surface is subjected to flame heat treatment or laser heat treatment to eliminate residual stress, the heat treatment temperature is 100 to 500°C, and the heat treatment time is 0.1 to 5 hours; after the coating cools to room temperature, the surface is polished, and the polishing method includes mechanical flat grinding, sandpaper or grinding wheel polishing. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the preparation method of the anti-steam erosion protective coating of the present invention. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0036] An embodiment of the present invention provides an anti-steam erosion protective coating, comprising at least four layers, each layer being prepared by laser printing from a composite powder, and taking the total mass of the composite powder as 100%, the composite powder comprises component A, component B and optionally component C, and in each layer of the composite powder, the mass fraction of component A decreases from the bottom layer to the surface layer, and the mass fraction of component B increases from the bottom layer to the surface layer, and the mass fraction difference of component B between adjacent layers is 1 to 25%; the component A comprises at least one of an Fe-based alloy, a Ni-based alloy, a Co-based alloy, and a high-entropy alloy, the component B comprises at least one of a carbide, an oxide, a nitride or a boride and optionally a bonding alloy, and the component C is a rare earth oxide.
[0037] Working principle: First, the present invention designs the above-mentioned gradient alloy material according to the principle of "tough inside and hard outside". The alloy materials with different "concentrations" make the surface layer of the coating have a higher hardness to resist mud and sand cutting wear; the internal alloy has a higher elastic modulus and good strong plasticity, which can play the role of elastic buffer or tissue phase change to absorb cavitation impact energy. Therefore, the coating exhibits "tough inside and hard outside" anti-steam erosion performance. Secondly, the coating has at least 4 layers, that is, component B has at least 4 different mass fractions, and the mass fraction difference of component B between adjacent layers is 1-25%. The coating has good bonding and matching between the layers, making the tissue performance more uniform and the coating has excellent anti-steam erosion performance; in addition, the present invention prepares a gradient alloy material coating on the surface of the protective substrate by laser printing method, which has excellent characteristics such as high metallurgical bonding strength and good toughness, and solves the problems of poor anti-steam erosion coupling damage and easy peeling failure existing in the current coating.
[0038] Component A is the main material, which plays a supporting role for the coating as a whole. Its elastic modulus, strength and toughness and plasticity are better than those of the component material, or it can undergo organizational changes or phase transformation strengthening under the impact of mechanical force to improve its ability to resist impact loads. One or more of Fe-based alloys, Ni-based alloys, Co-based alloys, high-entropy alloys, etc. can be selected, and the types include multi-reinforced alloys, amorphous alloys, shape memory alloys, intermetallic compound alloys, self-fluxing alloys, etc. Specifically, in addition to being able to resist plastic deformation caused by impact loads, iron-based amorphous alloys can also absorb energy and transform from amorphous phases to nanocrystalline, and then peel off and damage to resist cavitation. Cobalt-based alloys at room temperature are usually non-stable face-centered cubic structures (γ-fcc), which have extremely low stacking fault energy. Under the impact of mechanical force, γ-fcc→ε-hcp phase transformation can also occur, making them have high toughness, high yield strength and excellent fatigue resistance to resist cavitation. Nitinol and high-entropy alloys have high elastic modulus and can elastically buffer and dissipate cavitation impact energy.
[0039] Component B is a strengthening material, which plays a role in strengthening component A. The "concentration" of component B is distributed in a positive gradient from the bottom layer to the surface layer of the coating, so that each part of the coating shows different hardness and toughness properties. Hard materials such as carbides, nitrides, borides, oxides, etc. with high hardness can be selected. Preferably, the hardness of component B reaches more than 1000HV. As for the specific types used by component B, they include but are not limited to WC, Cr3C2, SiC, TiC, BN, TiN, SiB6, Al2O3, SiO2, TiO2, etc. The above types of component B belong to hard ceramic materials, which can be well wetted by component A, and can form a uniform composite powder with component A to enhance the wear resistance of the surface of the metal material. In addition, in order to improve the wettability, bonding and uniformity of components A and B, component B can appropriately increase bonding alloys such as Ni, Co, Cr, such as component B is WC-Co, WC-Co-Cr, NiCr-Cr3C2, etc.
[0040] Component C is an auxiliary material, which mainly promotes the uniform compounding of component A and component B and effectively refines the coating structure. Secondly, it also has the functions of reducing the content of harmful oxygen and sulfur elements in the coating, filling and reducing the pore defects in the coating, etc. One or more rare earth oxide materials can be selected. As for the specific types of component C, they include but are not limited to La2O3, CeO2, Y2O3, Er2O3, etc.
[0041] In the coating of the present invention, component B has at least 4 mass fractions, and the mass fraction difference of component B between adjacent layers is 1-25%; correspondingly, component A also has at least 4 mass fractions, and the mass fraction difference of component A between adjacent layers is 1-25%. Too small a mass fraction difference of component B between layers will lead to the homogenization of coating performance, and it will not be able to simultaneously show the anti-steam erosion performance of "tough inside and hard outside"; too few layers and too large a mass fraction difference of component B between layers will lead to an excessively high hardness gradient, a sharp decrease in toughness, plasticity and bonding strength, and the coating will be susceptible to cavitation erosion fatigue fracture failure.
[0042] In some embodiments, preferably, the coating has 4 to 15 layers, that is, component B has 4 to 15 mass fractions. It should be noted that when component B is 0%, 0% is also calculated within these 4 to 15 mass fractions. Within this range of layers, the coating hardness gradient transition is uniform, and the toughness, plasticity and bonding strength decrease gently, but the coating performance does not tend to be homogenized. Therefore, the obtained coating has better steam erosion resistance. More preferably, the coating has 5 to 13 layers, that is, component B has 5 to 13 mass fractions.
[0043] In one possible embodiment, the mass fraction of component B changes from the bottom layer to the surface layer in an arithmetic progression, and the tolerance is 3 to 10%, preferably 4 to 6%. In another possible embodiment, the mass fraction of component B changes from the bottom layer to the surface layer in a non-arithmetic progression, and the difference in mass fraction of component B between adjacent layers is 1 to 25%, preferably 3 to 15%. In the above two embodiments, the embodiment of the present invention preferably changes in an arithmetic progression, which is more conducive to providing the bonding and matching between the layers of the overall coating, making the organizational performance more uniform, and the continuous gradient synergistic change ability better, and ultimately enhancing the coating's resistance to steam erosion coupling damage.
[0044] In some embodiments, in the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 96-100%, and the mass fraction of component B is 0-2.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 20-70%, and the mass fraction of component B is 30-80%. If the mass fraction of component B in the bottom layer is higher than 2.5%, the mass fraction of component A will be reduced accordingly, which may lead to a decrease in the elastic modulus, strength and toughness and plasticity inside the coating, thereby weakening the coating's ability to resist impact loads. If the mass fraction of component B in the surface layer is lower than 30%, the hardness of the surface layer of the coating may be insufficient, and the wear resistance may be greatly reduced; if the mass fraction of component B in the surface layer is greater than 80%, the fatigue toughness of the coating may decrease, the brittleness may increase, and it may not be able to effectively resist cavitation high-frequency impact.
[0045] In order to better balance the relationship between hardness, toughness and elasticity, and further improve the comprehensive anti-steam erosion performance of the coating, preferably, in the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 96-100%, and the mass fraction of component B is 0-2.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 38-54%, and the mass fraction of component B is 46-62%.
[0046] In order to better balance the relationship between hardness, toughness and elasticity and further improve the comprehensive anti-steam erosion performance of the coating, it is more preferred that in the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 98-100%, and the mass fraction of component B is 0-0.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 40-51%, and the mass fraction of component B is 48-60%.
[0047] In some embodiments, the mass fraction of component C is 0-4% based on the total mass of the composite powder as 100%. If the mass fraction of component C is higher than 4%, the content of component A and / or component B is reduced accordingly, and the coating cannot be guaranteed to have excellent anti-steam erosion ability. Preferably, the mass fraction of component C is 0-2%. More preferably, the mass fraction of component C is 0-1.5%. In addition, in the coating of the embodiment of the present invention, the mass fraction of component C added in each layer can be the same or different, as long as the above content range is met.
[0048] In some embodiments, the average particle size of component A is in the range of 50 to 200 μm, the average particle size of component B is in the range of 50 μm or less, and the average particle size of component C is in the range of 20 μm or less. The above particle size range allows component A, component B, and optionally component C to have a reasonable particle size match, which is beneficial to coating formation, and is also beneficial to improving the density of the coating, further improving the anti-steam erosion performance of the coating. Preferably, component C is nanoparticle size.
[0049] The present invention also provides a method for preparing a steam erosion resistant protective coating. Figure 1 As shown, the preparation method comprises the following steps:
[0050] (1) Preparation of composite powder: Component A, component B and component C are placed in three powder storage tanks respectively, and the control device sprays the component A, component B and optional component C in a specified mass ratio into the mixing tank in multiple times according to the set program, and the composite powders with a series of content ratios are formed after being stacked multiple times; or the composite powders with a series of content ratios are directly and continuously input into the laser printing device without passing through the powder storage tank;
[0051] (2) Surface treatment of energy components: The damaged parts of energy components are first repaired by welding or laser printing and then processed to be smooth. The surface is then derusted and degreased, and dried for use.
[0052] (3) Laser printing: The laser printing device is configured to be a front and rear dual laser series mode, wherein the front laser performs laser preheating on the surface of the energy component or the upper layer of the coating, and the rear laser adopts a coaxial powder feeding laser printing mode to prepare a coating on the surface area of the energy component that is fully preheated. The composite powders with a series of content ratios are rapidly melted, sintered or solidified and sequentially superimposed to prepare a metallurgical composite material with a gradient distribution characteristic;
[0053] (4) Optionally, coating strengthening treatment: performing stress removal and surface polishing treatment on the coating.
[0054] In step (1), components A, B, and C are placed in three feed tanks respectively, and the automatic control device sprays powders of different mass proportions into the mixing tank in multiple times according to the set program, and then forms gradient powders by continuous multiple superposition. This mixing method is simple and easy to control, and the continuous controllability of the powder gradient is good, which avoids uneven changes in the gradient caused by too much or too little powder. During this period, the previous powder is quickly mixed and evenly transferred to the powder storage tank of the laser printing device, and the powder with the mass proportion adjusted in the latter time is also mixed and falls into the powder storage tank, and the gradient powder is formed after continuous multiple superposition; it is also possible to directly input the gradient mixed powder into the laser printing device in sequence without passing through the powder storage tank. The preferred mixing method is electromagnetic stirring or mechanical ball milling.
[0055] In step (2), the specific operations of laser printing to repair and protect the parts are as follows: ① Pre-clean the repair area; ② Prepare laser printing powder and equipment, and convert the three-dimensional model of the repair and protection area into the movement path of the robot; ③ Determine the laser printing parameters, and perform laser printing on the surface of the part after the robot is positioned; ④ Heat treatment and surface treatment of the strengthening area of the part. The damaged part position is processed flat after laser printing repair, and is repeatedly cleaned with acetone and metal cleaning agent to remove rust, oil and other impurities on the surface of the part, and then dried for use.
[0056] In step (3), the powder is continuously input into a laser printing device to print and form a gradient coating material. The laser printing process has a high degree of automation, is flexible and controllable, and the coating has high metallurgical bonding strength, few defects and a low dilution rate, which is suitable for coating protection of parts with complex shapes.
[0057] The laser printing device is a front and rear dual laser series mode. The front laser first preheats the surface of the component or the upper layer of the coating to increase the bonding between the surface and the coating or between layers and reduce the tendency of thermal stress cracking of the coating. To avoid local deformation, the preheating temperature is generally not higher than 200°C. Then, in the rear laser, coaxial powder feeding laser printing is used to prepare the coating on the preheated surface area of the component. The gradient powder is quickly melted, sintered or solidified and superimposed in sequence to prepare a metallurgical composite material with a "concentration" gradient distribution characteristic. The laser printing process can choose whether to use gas protection according to actual needs. The preferred protective gas is an inert gas such as argon and helium.
[0058] In step (3), the preheating temperature of the front laser is 80-200°C, the rear laser adopts CO2 laser or YAG laser, and the process parameters of the rear laser are set as follows: laser power is 0.5-8KW, spot size is Φ0.5-5mm, scanning rate is 0.1-10m / min, overlap rate is 30%-80%, powder feeding speed is 5-100g / min, single pass printing thickness is 0.1-2.0mm, total coating thickness is 0.2-20mm, and inert gas protection is optional. Due to the different proportions of components in the gradient powder, preferably, the bottom layer laser power is 0.5-3KW, and the laser power between adjacent gradients differs by 0.1-0.5KW. The variable laser power can reduce interlayer defects and ensure that the gradient powder can be more effectively fused.
[0059] In step (4), after laser printing is completed, the coating is subjected to stress removal and surface grinding treatment to effectively reduce the impact of residual stress and roughness on the performance of the component. Specifically, after the powder is solidified by high-temperature quenching to form a surface coating, there will be large residual stress, which can easily cause the coating to crack and fall off. The coating surface can be treated with flame heat treatment or laser heat treatment to eliminate residual stress and ensure that the component has no thermal deformation. The heat treatment temperature is 100 to 500°C and the heat treatment time is 0.1 to 5 hours. After the coating is cooled to room temperature, it is subjected to surface grinding treatment to ensure surface smoothness and remove some defects such as protrusions and pores, so that the surface roughness of the coating meets the component requirements. Specific grinding methods include mechanical flat grinding, sandpaper or grinding wheel grinding, etc.
[0060] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0061] Example 1: Ni60AACuMo / WC-12Co gradient material
[0062] (1) Powder preparation. Component A is Ni60AACuMo (nickel-based self-fluxing alloy) with an average particle size range of 100-120 μm; component B is WC-12Co with an average particle size range of 25-45 μm; component C is absent. A certain mass of components A and B are placed in two feed tanks. The control device sprays powders of different mass ratios into the mixing tank in multiple times according to the set program, and then mixes them evenly through electromagnetic stirring and falls into the powder storage tank. Gradient powder is formed after multiple superpositions. Among them, the mass fraction ratio of the first component A and B is 100%:0%, and the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 10%. The mass fraction ratio of the last component A and B is 40%:60%. The sum of the mass fractions of the two remains unchanged at 100% during the process. It should be noted that WC-12Co represents the Co content of 12% based on the total mass of component B as 100%.
[0063] (2) Component surface treatment. The damaged parts are repaired by welding or laser printing and then processed to be flat. They are then repeatedly cleaned with acetone and metal cleaning agent to remove rust, oil and other impurities on the surface of the energy components, and then dried for use.
[0064] (3) Laser printing. The front laser first preheats the surface of the energy component at a preheating temperature of 120°C. The rear laser uses coaxial powder feeding laser printing to prepare a coating on the preheated surface area of the energy component. The gradient powder is quickly melted, sintered or solidified and stacked in sequence to form a gradient material. The main process parameters of the rear laser are: YAG laser, the initial layer laser power is 2KW, and the subsequent layers increase in an arithmetic progression with a tolerance of 0.1KW; the spot size is Φ1mm, the scanning rate is 0.3m / min, the overlap rate is 50%, the single-pass printing thickness is about 0.4mm, and argon protection is used. Finally, a 7-layer composite coating material with a surface layer of 40% Ni60AACuMo-60% WC-12Co, a bottom layer of 100% Ni60AACuMo-0% WC-12Co, and a gradient distribution of the intermediate layer composition and excellent metallurgical bonding performance is obtained.
[0065] (4) Residual stress removal and surface grinding. The flame heat treatment temperature is 250°C, the moving speed is 0.5m / min, and the time is 0.5h. Mechanical flat grinding is used to remove surface defects such as protrusions and pores. Finally, the gradient material coating thickness is 2.4mm and the surface roughness is Ra1.6.
[0066] Example 2: NiTi / Cr3C2 / La2O3 gradient material
[0067] (1) Powder preparation. Component A is NiTi (nickel-coated titanium intermetallic compound powder) with an average particle size range of 80-100 μm; component B is Cr3C2 with an average particle size range of 15-25 μm; component C is La2O3 with an average particle size range of 5-10 μm. A certain mass of components A, B, and C are placed in two feed tanks. The control device sprays powders of different mass ratios into the mixing tank in multiple times according to the set program, and then mixes them evenly through electromagnetic stirring and falls into the powder storage tank. Gradient powder is formed after multiple stacking. Among them, the mass fraction ratio of the first components A, B, and C is 99%: 0%: 1%, and the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 6%. Component C does not change, and the mass fraction ratio of the last components A, B, and C is 51%: 48%: 1%. The sum of the mass fractions of the three components remains unchanged at 100% during the process.
[0068] (2) Component surface treatment. The damaged parts are repaired by welding or laser printing and then processed to be flat. They are then repeatedly cleaned with acetone and metal cleaning agent to remove rust, oil and other impurities on the surface of the energy components, and then dried for use.
[0069] (3) Laser printing. The front laser first preheats the surface of the energy component at a preheating temperature of 150°C. The rear laser uses coaxial powder feeding laser printing to prepare a coating on the preheated surface area of the energy component. The gradient powder is quickly melted, sintered or solidified and stacked in sequence to form a gradient material. The main process parameters of the rear laser are: YAG laser, the initial layer laser power is 2.5KW, and the subsequent layers increase in an arithmetic progression with a tolerance of 0.1KW; the spot size is Φ2mm, the scanning rate is 1m / min, the overlap rate is 40%, the single-pass printing thickness is about 0.2mm, and argon protection is used. Finally, a 9-layer composite coating material with a surface layer of 51% NiTi-48% Cr3C2-1% La2O3, a bottom layer of 99% NiTi-0% Cr3C2-1% La2O3, and a middle layer with a gradient distribution of components and excellent metallurgical bonding properties is obtained.
[0070] (4) Removal of residual stress and surface polishing. The laser heat treatment temperature was 300°C, the moving speed was 0.2 m / min, and the time was 1 h. The grinding wheel and sandpaper method was used to remove surface defects such as protrusions and pores. Finally, the gradient material coating thickness was 1.6 mm and the surface roughness was Ra3.2.
[0071] Example 3: Stellite6 / Al2O3 / CeO2 gradient material
[0072] (1) Powder preparation. Component A is Stellite6 (cobalt-based multi-element alloy powder) with an average particle size range of 60-80μm; component B is Al2O3 with an average particle size range of 8-15μm; component C is CeO2 with an average particle size range of 5-10nm. A certain mass of components A, B, and C are placed in two feed tanks. The control device sprays powders of different mass ratios into the mixing tank in multiple times according to the set program, and then mixes them evenly through electromagnetic stirring and falls into the powder storage tank. Gradient powder is formed after multiple superposition. Among them, the mass fraction ratio of the first components A, B, and C is 98%: 0.5%: 1.5%, and the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 4%. Component C does not change, and the mass fraction ratio of the last components A, B, and C is 50%: 48.5%: 1.5%. The sum of the mass fractions of the three components remains unchanged at 100% during the process.
[0073] (2) Component surface treatment. The damaged parts are repaired by welding or laser printing and then processed to be flat. They are then repeatedly cleaned with acetone and metal cleaning agent to remove rust, oil and other impurities on the surface of the energy components, and then dried for use.
[0074] (3) Laser printing. The front laser first preheats the surface of the energy component at a preheating temperature of 160°C. The rear laser uses coaxial powder feeding laser printing to prepare a coating on the preheated surface area of the energy component. The gradient powder is quickly melted, sintered or solidified and stacked in sequence to form a gradient material. The main process parameters of the rear laser are: CO2 laser, the initial layer laser power is 3KW, and the subsequent layers increase in an arithmetic progression with a tolerance of 0.2KW; spot size Φ1mm, scanning rate 5m / min, overlap rate 70%, single-pass printing thickness of about 0.1mm, argon protection. Finally, a 13-layer composite coating material with a surface layer of 50% Stellite6-48.5% Al2O3-1.5% CeO2, a bottom layer of 98% Stellite6-0.5% Al2O3-1.5% CeO2, and a gradient distribution of the middle layer composition and excellent metallurgical bonding performance is obtained.
[0075] (4) Removal of residual stress and surface polishing. The flame heat treatment temperature is 300°C, the moving speed is 0.1m / min, and the time is 2h. The grinding wheel and sandpaper method are used to remove surface defects such as protrusions and pores. Finally, the gradient material coating thickness is 1.2mm and the surface roughness is Ra3.2.
[0076] Example 4: Ni60AACuMo / WC-12Co gradient material
[0077] The method is the same as that in Example 1, except that in step (1), the mass fraction ratio of the first components A and B is 97%:3%, the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 10%, and the mass fraction ratio of the final components A and B is 37%:63%.
[0078] Example 4: A 7-layer composite coating material with a surface layer of 37% Ni60AACuMo-63% WC-12Co, a bottom layer of 97% Ni60AACuMo-3% WC-12Co, and a gradient distribution of the intermediate layer was finally obtained, with a thickness of 2.4 mm.
[0079] Example 5: Ni60AACuMo / WC-12Co gradient material
[0080] The method is the same as that in Example 1, except that in step (1), the mass fraction ratio of the first components A and B is 100%:0%, the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 10%, and the mass fraction ratio of the last components A and B is 30%:70%.
[0081] Example 5 finally obtained an 8-layer composite coating material with a surface layer of 30% Ni60AACuMo-70% WC-12Co, a bottom layer of 100% Ni60AACuMo-0% WC-12Co, and a middle layer with a gradient distribution of components, and a thickness of 2.4 mm.
[0082] Comparative Example 1: ZG06Cr13Ni4Mo martensitic stainless steel (commonly used hydropower steel)
[0083] Comparative Example 2: WC-10Co-4Cr thermal spraying material
[0084] Comparative Example 3: Ni60AACuMo / WC-12Co gradient material
[0085] The method is the same as that in Example 1, except that in step (1), the mass fraction ratio of the first components A and B is 96%:4%, the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 10%, and the mass fraction ratio of the last components A and B is 76%:24%.
[0086] Comparative Example 3 finally produced a three-layer composite coating material with a surface layer of 76% Ni60AACuMo-24% WC-12Co, a middle layer of 86% Ni60AACuMo-14% WC-12Co, and a bottom layer of 96% Ni60AACuMo-4% WC-12Co, with a thickness of 2.4 mm.
[0087] Comparative Example 4: Ni60AACuMo / WC-12Co gradient material
[0088] The method is the same as that in Example 1, except that in step (1), the mass fraction ratio of the first components A and B is 100%:0%, the mass fractions of the subsequent components change in an arithmetic progression with a tolerance of 30%, and the mass fraction ratio of the last components A and B is 40%:60%.
[0089] Comparative Example 4 finally produced a three-layer composite coating material with a surface layer of 40% Ni60AACuMo-60% WC-12Co, a middle layer of 70% Ni60AACuMo-30% WC-12Co, and a bottom layer of 100% Ni60AACuMo-0% WC-12Co, with a thickness of 2.4 mm.
[0090] The relevant materials used in the above embodiments and comparative examples can be purchased commercially or prepared by themselves.
[0091] The coatings obtained in Examples 1-5 and Comparative Examples 1-4 were subjected to surface hardness tests and cavitation resistance tests, and the test results are recorded in Table 1. The surface hardness test was conducted in accordance with GB / T 4340.1-1999 "Metal Vickers Hardness Test Part 1: Test Method", and the cavitation resistance test was conducted in accordance with GB / T 6383-2009 "Vibration Cavitation Test Method".
[0092] Table 1 Performance test results of coatings of Examples 1-5 and Comparative Examples 1-4
[0093]
[0094]
[0095] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0096] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A steam erosion resistant protective coating, characterized in that: The coating comprises at least five layers, each layer is prepared by laser printing of composite powder, the total mass of the composite powder is 100%, the composite powder comprises component A and component B and optionally component C, in each layer of the composite powder, the mass fraction of component A decreases from the bottom layer to the surface layer, the mass fraction of component B increases from the bottom layer to the surface layer, and the mass fraction difference of component B between adjacent layers is 1-10%; the component A comprises at least one of Fe-based alloy, Ni-based alloy, Co-based alloy and high entropy alloy, the component B comprises at least one of carbide, oxide, nitride or boride and optionally adhesive Combining alloy, the component C is a rare earth oxide; in the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of the component A is 98-100%, and the mass fraction of the component B is 0-2.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of the component A is 20-70%, and the mass fraction of the component B is 30-80%; the carbide includes at least one of WC, Cr3C2, SiC, and TiC, the nitride includes BN and / or TiN, and the boride includes at least one of SiB6, Al2O3, SiO2, and TiO2.
2. The anti-steam erosion protective coating according to claim 1, characterized in that: The coating layer has 5 to 15 layers.
3. The anti-steam erosion protective coating according to claim 2, characterized in that: The coating has 5 to 13 layers.
4. The anti-steam erosion protective coating according to claim 1 or 2, characterized in that: The mass fraction of the component B changes in an arithmetic progression from the bottom layer to the surface layer, and the tolerance is 3-10%.
5. The anti-steam erosion protective coating according to claim 1, characterized in that: In the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 98-100%, and the mass fraction of component B is 0-2.5%; in the surface layer, the mass fraction of component A is 38-54%, and the mass fraction of component B is 46-62%.
6. The anti-steam erosion protective coating according to claim 5, characterized in that: In the bottom layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 98-100%, and the mass fraction of component B is 0-0.5%; in the surface layer, based on the total mass of the composite powder as 100%, the mass fraction of component A is 40-51%, and the mass fraction of component B is 48-60%.
7. The anti-steam erosion protective coating according to claim 1 or 2, characterized in that: Based on the total mass of the composite powder being 100%, the mass fraction of the component C is 0-4%.
8. The anti-steam erosion protective coating according to claim 7, characterized in that: The mass fraction of the component C is 0-2%.
9. The anti-steam erosion protective coating according to claim 1 or 2, characterized in that: The average particle size range of the component A is 50 to 200 μm, the average particle size range of the component B is less than or equal to 50 μm, and the average particle size range of the component C is less than or equal to 20 μm.
10. The anti-steam erosion protective coating according to claim 9, characterized in that: The component C is nano-particle size.
11. The anti-steam erosion protective coating according to claim 1, characterized in that: The bonding alloy includes at least one of Ni, Co, and Cr bonding alloys, and the rare earth oxide includes at least one of La2O3, CeO2, Y2O3, and Er2O3.
12. The method for preparing the anti-steam erosion protective coating according to any one of claims 1 to 11, characterized in that: The following steps are involved: (1) Preparation of composite powder: Component A, component B and component C are placed in three powder storage tanks respectively, and the control device sprays the component A, component B and optional component C in a specified mass ratio into the mixing tank in multiple times according to the set program, and the composite powders with a series of content ratios are formed after being stacked multiple times; or the composite powders with a series of content ratios are directly and continuously input into the laser printing device without passing through the powder storage tank; (2) Surface treatment of energy components: The damaged parts of energy components are first repaired by welding or laser printing and then processed to be smooth. The surface is then derusted and degreased, and dried for use. (3) Laser printing: The laser printing device is configured to be a front and rear dual laser series mode, wherein the front laser performs laser preheating on the surface of the energy component or the upper layer of the coating, and the rear laser adopts a coaxial powder feeding laser printing mode to prepare a coating on the surface area of the energy component that is fully preheated. The composite powders with a series of content ratios are rapidly melted, sintered or solidified and sequentially superimposed to prepare a metallurgical composite material with a gradient distribution characteristic; (4) Optionally, coating strengthening treatment: performing stress removal and surface polishing treatment on the coating.
13. The method for preparing the anti-steam erosion protective coating according to claim 12, characterized in that: In step (3), the preheating temperature of the front laser is 80-200°C, the rear laser adopts a CO2 laser or a YAG laser, and the process parameters of the rear laser are set as follows: laser power is 0.5-8kW, spot size is Φ0.5-5mm, scanning rate is 0.1-10m / min, overlap rate is 30%-80%, powder feeding speed is 5-100g / min, single pass printing thickness is 0.1-2.0mm, total coating thickness is 0.2-20mm, and inert gas protection is optional.
14. The method for preparing the anti-steam erosion protective coating according to claim 13, characterized in that: In step (3), the bottom layer laser power is 0.5 to 3 kW, and the subsequent layer laser power increases in an arithmetic progression with a tolerance of 0.1 to 0.5 kW.
15. The method for preparing the anti-steam erosion protective coating according to claim 12, characterized in that: In step (4), the coating surface is subjected to flame heat treatment or laser heat treatment to eliminate residual stress, the heat treatment temperature is 100 to 500°C, and the heat treatment time is 0.1 to 5 hours; after the coating cools to room temperature, the surface is polished, and the polishing method includes mechanical flat grinding, sandpaper or grinding wheel polishing.
Citation Information
Patent Citations
Method with functions of preheating and postheating for forming crack-free coating with high efficiency by three-light-beam laser-cladding technique
CN102383126A
Induction-cladded gradient hard composite material coating technique
CN104894558A